Haushaltskonsolidierungsstrategien im Vergleich. Warum die deutsch-europaeische Fiskalpolitik versagt - Jörg Bibow (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
– This paper analyses the issues of public finance sustainability and suitability of strategies aimed at fiscal consolidation, contrasting growth-based versus thriftbased strategies. Empirically, this study investigates the experiences with consolidation over the 1990s in the U.S., Japan, and the eurozone while scrutinizing disparities within Europe. It is argued that neither Germany's virtuous stability-oriented past, which in many ways provided the blueprint for the Maastricht regime's design, nor any other small economy's peculiar record with consolidation offers any guidance to the EMU today. For that purpose only the case of the US case may be relevant, featuring cooperative macroeconomic policies geared at steering domestic demand growth, with sustainable public finances as a consequence of their success. Reforms should thus focus on securing cooperation and proper growth orientation in macroeconomic policymaking, which may be achieved through committing fiscal and monetary policies to common goals and a nominal GDP targeting strategy.
Keywords: E58; E61; E62; E63; E65; 330